1-Methyl-2-({[(2-methylphenyl)methyl]-disulfanyl}methyl) benzene. - Tayamon, Shahedeh; S. A. Ravoof, Thahira Begum; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne; Tiekink, Edward R. T. (International Union of Crystallography, 2012)
In the title disulfide, C16H18S2, the molecule is twisted about the central S—S bond [the C—S—S—C torsion angle = 93.24 (7)°] and the dihedral angle between the benzene rings is 72.84 (7)°, indicating an almost orthogonal relationship; the methyl groups are orientated to the same side of the molecule. The crystal packing features C—H(...).π interactions which consolidate a three-dimensional architecture.